Pemanfaatan Arang Aktif Ampas Kopi Arabika (Coffea arabica) dengan Aktivator Asam Klorida (HCl) dan Asam Fosfat (H3PO4) Sebagai Adsorben Logam Kromin (Cr) pada Limbah Tekstil - Dody Guntama; Mubarokah Nuriani Dewi; Lukman Nulhakim; Samuel Armawan Sandi; Audina Trisnaeni; Ayu Lintang (LPPM Institut Teknologi Petroleum Balongan, 2023)
Activated charcoal of Arabica coffee grounds with different activators (HCl and H3PO4) has the potential as an adsorber for chromium in artificial textile waste. Coffee grounds can be used as raw material for activated charcoal because it has a fairly high carbon content. Waste is made using Chromic Acid powder with a ratio of 1:10 to Aquadest. The concentrations of HCl and H3PO4 activators used were respectively 0.1 N. Activated charcoal is made by drying coffee grounds for 24 hours and the carbonization process is carried out in a furnace at a temperature of 200 oC. Charcoal formed is activated with HCl and 0.1 N H3PO4 activator for 48 hours. The characteristics tested were ash content, water content, absorption of iodine, and absorption of chromium solution. The chromium absorption test used AAS (Atomic Absorption Spectrophotometry) and SEM-EDX (Scanning Electron Microscope - Energy Dispersive X-Ray) tests. The results showed that Arabica coffee grounds had the potential as chromium adsorbent and the best activator used was HCl with the characteristics of activated charcoal as follows: water content of 8.1175%, ash content of 4.5981%, absorption of iodine of 401.7964 mg /g and the absorption capacity of chromium solution is 800 mg/g.